Improving Crop Productivity, Nutrient Use Efficiency and Economics of Chamomile (Matricaria chamomilla L.) Using Phosphate and Potassium Solubilizing Bacteria - Prakhyath, K M; Mehra, Priyanka; Khatri, Charul; Prakash, T Arul; Kumar, Dipender; Padalia, R C; Yogendra, N D (Fundamental and Applied Agriculture, 2024)
Chamomile (Matricaria chamomilla L.) is a vital medicinal and aromatic plant, widely recognized for its industrial applications. However, sustainable cultivation of chamomile faces challenges due to the excessive use of chemical fertilizers, which can negatively impact soil health and the environment. There is a growing need to explore alternative agricultural practices that enhance nutrient use efficiency while minimizing environmental harm. Field experiments were conducted from 2022 to 2024 at the CSIR-CIMAP Research Centre in Bengaluru to evaluate the effects of Phosphate Solubilizing Bacteria (PSB) and Potassium Solubilizing Bacteria (KSB) on the performance and nutrient use efficiency of chamomile. Various treatment combinations of Recommended Dose of Fertilizers (RDF: 100 kg N, 60 kg P2O5, and 40 kg K2O ha-1) with PSB and KSB were tested, including co-inoculation and sole applications, to determine their impact on plant growth, yield and economic returns. Co-inoculating PSB and KSB with 100% RDF significantly increased plant height (48.09 cm) and branch count (15.43), outperforming RDF alone and other treatments. Sole applications of PSB or KSB with 100% RDF were comparable to 75% RDF combinations. The highest agronomic use efficiency (27.28%) and microbial response (37.49%) were achieved with 100% RDF+PSB+KSB, leading to a 137.49% yield increase. The highest concentrations of key compounds, α-bisabolol oxide B and α-bisabolol, were observed with 75% RDF+PSB+KSB. α-bisabolol peaked in the RDF-alone treatment. The 100% RDF+PSB+KSB treatment achieved the highest net monetary returns (US 5110 ha-1) and a benefit-to-cost ratio of 2.41, similar to 75% RDF+PSB+KSB. Overall, 75% RDF with PSB and KSB significantly enhances chamomile performance, increases soil bacterial populations, boosts nutrient mineralization, reduces chemical fertilizer use, and minimizes environmental impact. This approach offers a promising pathway for sustainable chamomile cultivation, leading to higher yields, improved economic returns, and reduced environmental impact.